Case study—Characterizing and averting risk of catastrophic vessel failure for a reaction in dimethyl sulfoxide. Issue 2 (14th June 2019) - Roth, Megan
Abstract: Process safety testing performed on a batch process for making a pharmaceutical intermediate revealed that one process stream, a reaction in dimethyl sulfoxide, had a significant undesired reaction that could lead to catastrophic vessel failure as a result of a single process deviation. Comprehensive testing identified the worst case process stream with the lowest exotherm initiation temperature and most severe pressure consequences, for which corrective actions must be taken. With this information in hand, hazard assessments were performed to support processing, to determine the appropriate safeguards needed to mitigate the consequences, and to reduce the likelihood of reaching this activity to a tolerable level.